BRAC University: building a 21st century library - Afroz, Hasina (The Daily Star, Star Campus, 2014)
The writer is Senior Deputy Librarian (Head of Library), BRAC University and Project Director, BRAC University Institutional Repository, ILS and Discovery Tool Project